2013
DOI: 10.1016/j.bmcl.2013.01.107
|View full text |Cite
|
Sign up to set email alerts
|

Improved guanide compounds which bind the CXCR4 co-receptor and inhibit HIV-1 infection

Abstract: The G-protein coupled receptor CXCR4 is a co-receptor for HIV-1 infection and is involved in signaling cell migration and proliferation. In a previous study of non-peptide, guanide-based CXCR4-binding compounds, spermine and spermidine phenylguanides inhibited HIV-1 entry at low micromolar concentrations. Subsequently, crystal structures of CXCR4 were used to dock a series of naphthylguanide derivatives of the polyamines spermidine and spermine. Synthesis and evaluation of the naphthylguanide compounds identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…2 , compounds 7–9 ). For example, compound 7 is a close structural analog of KRH-1636 (EC 50 = 18 nM), 34 compound 8 contains a presumable CXCR4-binding guanidine moiety, 35 and compound 9 expresses a secondary amine pattern that is observed in structurally related potent CXCR4 antagonists. 32 The random forest SAR model rightfully lacked confidence regarding the activity of these inactive analogues, which suggests that they are valuable for improving the understanding of the SAR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 , compounds 7–9 ). For example, compound 7 is a close structural analog of KRH-1636 (EC 50 = 18 nM), 34 compound 8 contains a presumable CXCR4-binding guanidine moiety, 35 and compound 9 expresses a secondary amine pattern that is observed in structurally related potent CXCR4 antagonists. 32 The random forest SAR model rightfully lacked confidence regarding the activity of these inactive analogues, which suggests that they are valuable for improving the understanding of the SAR.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, with their elongated shape and terminal aromatic rings, some of our hits seem to constitute hybrids of known CXCR4 ligands, suggesting that the model successfully generalized over the known SARs. We tested this hypothesis by investigating the reference compounds used for predicting the most potent thiourea compound 10 , and found that the model coupled this chemical structure with distinct types of CXCR4 antagonists, including diamines, 32 cyclam AMD3100 derivatives, 16 isothiourea 38 and guanidine-containing compounds 35 (Table S6 † ). The notable chemical similarity to known antagonists is attractive for model interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these compounds were previously found to be effective as antagonists of CXCR4 and inhibited HIV infection by X4 strains [4], [5] and the formation of metastatic tumors [6]. The biguanide series of compounds are chemically related to some commercially important biocidal agents found in common household items such as disinfectants, mouthwashes, contact lens solutions, and cosmetics.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of THAM-3ΦG described previously 60 was modified to increase compound yields as follows: 1-BOC hexanediamine (1 equiv.) was initially treated with S-methyl-phenylisourea (1.1 equiv.…”
Section: Methodsmentioning
confidence: 99%
“…in water and refluxed at 120 °C to obtain THAM-3ΦG. THAM-3ΦG was purified by preparative reverse phase HPLC as previously reported (95% acetonitrile, 95% H 2 O, and 0.1% TFA) 60 . THAM-3ΦG stocks were prepared at 5.33 mg/mL in 50% acetonitrile and H 2 O.…”
Section: Methodsmentioning
confidence: 99%